Pedagogical Mediation for early childhood during confinement - Solís Solís, Delía María; Ramírez Acuña, Gabriela (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
This article takes the statistical data thrown in the research "Analysis of the Self-regulation of emotions in children of maternal and child and transition, during the strategy" I learn at home "in times of SARS-Cov-2, and emphasizes the analysis in the pedagogical mediation carried out by the teacher. The statistical data made it possible to determine: the learning tools implemented, the number of classes per week, the number and form of activities carried out per week, the number of students per group, among others.